Strain partitioning along the Mahanadi Shear Zone: Implications for paleo-tectonics of the Eastern Ghats Province, India. (15th May 2018) - Bose, Subham; Gupta, Saibal
Graphical abstract: Highlights: Mahanadi Shear Zone post-dates granulite metamorphism in the Eastern Ghats Province. Field, microstructure and EBSD data indicate greenschist facies dextral shearing. Shearing operated in the greenschist facies before Gondwana sediment deposition. Abstract: During Indo-Antarctic collision at c. 1.0 Ga, Eastern Ghats Province (EGP) granulites amalgamated with the Archean Indian craton. The northern boundary of the EGP was subsequently reworked, undergoing dextral strike-slip shearing at 0.5 Ga. This study documents a phase of dextral shearing within the EGP along WNW-ESE trending shear planes in c. 0.5 Ga mylonites of the Mahanadi Shear Zone. Regional structural trends in the EGP show a swing from NE-SW to the south of the shear zone, to WNW-ESE to its north. The mylonitic shear zone foliation has a sub-horizontal lineation associated with a prominent dextral shear sense in near-horizontal sections. Electron Back Scatter Diffraction (EBSD) studies on quartz confirm that mylonitisation was associated with dextral strike-slip movement in the greenschist facies. North of the Mahanadi Shear Zone, strain was partitioned into narrow dextral strike-slip shear zones along which the older granulite fabrics were transposed parallel to later WNW-ESE trending shear planes at lower grades of metamorphism. This regional-scale shearing at ∼ 500 Ma possibly resulted in a significant dextral shift of the northern EGP with respect to the south. The shear zone was reactivated in the Permian time during deposition of Gondwana sediments in the Mahanadi basin.